Tourism and animal ethics - Fennell, David A., 1963- (New York, USA: Routledge, 2024)
"This timely book provides a critical account of the role that animals play in the tourism industry, representing an extension of the sustainability imperative and environmental theory. Offering an interdisciplinary overview of the moral issues related to the use of animals in tourism through cutting edge research, this book is essential reading for students, academics and researchers interested in tourism ethics, sustainable tourism and wildlife tourism"--
Previous edition published in 2012.
Includes bibliographical references and index.
Keywords: Tourism -- Moral and ethical aspects; Ecotourism; Animal welfare